REFLECȚII PRIVIND IMPLEMENTAREA UNOR MECANISME EFICIENTE ÎN DEZVOLTAREA ADMINISTRAȚIEI PUBLICE - Сodreanu, Valeria (CEP USM, 2020)
This article emphasizes the importance of reform in public administration, this being the most significant and important change in a society. Understanding and knowing the contradictions of the public administration reform helps us to choose the appropriate model and structure for the Republic of Moldova for a more efficient and sustainable form of government for a better life of citizens
Keywords: public administration; government; reforms; development